CO2 Storage in Depleted or Depleting Oil and Gas Fields: What can We Learn from Existing Projects?. (July 2017) - Hannis, Sarah; Lu, Jiemin; Chadwick, Andy; Hovorka, Sue; Kirk, Karen; Romanak, Katherine; Pearce, Jonathan
Abstract: Storing CO2 in depleted or depleting oil and gas fields has now been proven at a number of sites worldwide. Key risks have been overcome, for example, relating to site design for dealing with reduced reservoir pressure, re-using infrastructure and managing wellbore integrity risks. Despite this, large-scale "pure" CO2 storage in depleted fields remains to be tested and closure of a large-scale CO2 -EOR site has not yet occurred. It is hoped that dissemination of key learnings from these sites will encourage and inform discussions on CO2 storage in depleting fields elsewhere, to allow the early consideration necessary for exploitation of existing facilities (prior to decommissioning), and ultimately fill the short-term CO2 storage gap for quick (and relatively cheap) climate abatement returns until large-scale storage in saline aquifers can be fully implemented.